EHMT2‐mediated R‐loop formation promotes the malignant progression of prostate cancer via activating Aurora B - Yuyang Zhang; Mingqin Su; Yiming Chen; Li Cui; Wei Xia; Renfang Xu; Dong Xue; Xiansheng Zhang; Xingliang Feng (Clinical and Translational Medicine, 2025)
Abstract Background Chromosomal instability (CIN), a hallmark of cancer, is commonly linked to poor prognosis in high‐grade prostate cancer (PCa). Paradoxically, excessively high levels of CIN may impair cancer cell viability. Consequently, understanding how tumours adapt to CIN is critical for identifying novel therapeutic targets. Methods Bioinformatic analyses were conducted to identify genes overexpressed in PCa tissues using The Cancer Genome Atlas (TCGA) and GEO datasets. Western blotting and immunohistochemistry assays were applied to determine the expression levels of euchromatic histone lysine methyltransferase 2 (EHMT2), pT232‐Aurora B and Cullin 3 (CUL3). The proliferation of cells was measured through CCK‐8 tests, clonogenesis and subcutaneous xenografts of human PCa cells in BALB/c nude mice. Live cell imaging, immunofluorescence (IF) and flow cytometry were used to confirm the role of EHMT2 in PCa cell mitosis. Co‐immunoprecipitation, Western blotting and IF assays further elucidated the underlying molecular mechanisms. Results EHMT2 was highly expressed in metastatic PCa tissues exhibiting elevated CIN and was strongly associated with adverse clinical outcomes in patients with PCa. Silencing EHMT2 impaired cell division, inducing G2/M‐phase arrest and mitotic catastrophe in PCa cells. Mechanistically, EHMT2 is indispensable to ensure the full activation of Aurora B through centromeric R‐loop‐driven ATR–CHK1 pathway, with EHMT2 protein expression peaking during the G2/M‐phase. Moreover, CUL3 was identified as a binding partner of EHMT2, mediating its polyubiquitination and destabilising its protein levels. Conclusions This study reveals a CUL3–EHMT2–Aurora B regulatory axis that safeguards accurate chromosome segregation in PCa cells, supporting the potential therapeutic application of EHMT2 inhibitors. Key points Euchromatic histone lysine methyltransferase 2 (EHMT2) is overexpressed in advanced prostate cancer, restraining catastrophic chromosomal instability (CIN) and enhancing cell fitness. EHMT2 functions via the centromeric R‐loop‐driven ATR–CHK1–Aurora B pathway to promote chromosomal stability. EHMT2 confers enzalutamide resistance via activating Aurora B. Cullin 3 (CUL3) promotes EHMT2 destabilisation via deubiquitination.